PENGEMBANGAN BAHAN AJAR PENDIDIKAN AGAMA ISLAM (PAI) BERBASIS INTEGRASI SAINS DAN TEKNOLOGI PESERTA DIDIK KELAS X SMA IT AL MAWADDAH WARRAHMAH KOLAKA - Annisa, annisa; Umajjah, Nur Thahirah; Zakariah, Muhammad Askari (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
The quality of learning Islamic religious education will be better, if the learning does not focus on religious learning alone but is broad, both on science and technology. By combining this knowledge, it will further develop students' understanding of both the aspects of religion and science and technology. Based on this, this study aims to explain the Development of Islamic Religious Education (PAI) Teaching Materials Based on the Integration of Science and Technology for Class X Students of SMA IT Al Mawaddah Warrahmah Kolaka